A review on mitigation of various ailments via a bioactive component of Tribulus terrestris L. - A medicinally important herb - Chaudhary, Ashun; Kumari, Ruchika; Manisha; Thakur, Palak (Ethnobotany Research and Applications, 2023)
Background: Tribulus terrestris L. is an important traditional therapeutic plant that has been utilized for multiple purposes since the Vedic period and belong to Zygophyllaceae family. It is distributed in sub-tropical regions including India, China, New Zealand, Sri Lanka, and Pakistan. It is used in the Chinese medicine system for eye problems, sexual dysfunction, piles, and vesical calculi. It contains steroids, antioxidants, saponins, flavonoids, phenolics, alkaloids, proteins, and amino acids. Methods: The review was performed to gain detailed knowledge of this plant. The literature search was carried out by using various platforms like the online database PubMed, Science Direct, Google Scholar, Ayush, e-Charaka, SpringerLink, and books. Results: T. terrestris often referred to as Gokshur or Gokharu, has utilised in Indian, Unani and Chinese medicine to cure various illnesses from long time. The plant is known to have diuretic, aphrodisiac, anti-urolithic, immunomodulatory, hypolipidemic, antidiabetic, cardiotonic, antispasmodic, anti-inflammatory, analgesic, and hepatoprotective activities. It includes flavonol glycosides, flavonoids, steroidal saponins, and alkaloids. Phytochemicals present in plant include protodioscin, terrestrosins A, gitonin, tigogenin, β-sitosterol, and terrestrosins E, spirosta-3,5-diene, stigmasterol, diosgenin, hecogenin, kaempferol. It also possesses anti-cariogenic, antibacterial, anthelmintic, larvicidal, and anticancer activities. The aim of this study is to offer an outline of the pharmacological, medicinal and therapeutic potential of T. terrestris. Conclusion: From an extensive review of this plant, it is found that the plant is a rich source of phytochemicals and has high pharmacological values. Thus, it is concluded that this plant is highly medicinal and can be used as a potent source of drugs that are useful for mankind. The information documented in this paper will be helpful for industrial, medicinal, and commercial use. Keywords: Tribulus terrestris, Gokhru, Ayurveda, Pharmacological activities, Aphrodisiac, Larvicidal